The tapping and capping of human creativity: an Islamic perspective - Abdul Razak, Mohd Abbas; Machouche, Salah (Department of Communication, AHAS-Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), 2022)
Like human intelligence, creativity is diverse. In the beginning, the scientific investigation of human intelligence was mainly referred to as PQ (Physical Intelligence), later on, psychologists discovered other aspects of intelligence like IQ (Intellectual Intelligence), EQ (Emotional Intelligence) and the latest is SQ (Spiritual Intelligence). In a similar manner, creativity is not just confined to artworks. Of late, creativity is seen in the skillful use of language that produces good literary works, poetry, great movie dialogues, rhetoric etc. Besides language, the contemporary trend in looking at creativity also includes fields like culinary arts, fashion, music, management science, etc. In the industrialized and globalized world that we are living in today, there is a big demand for those embellished with the quality of being creative. As such, those who are not only book smart but also creative and innovative are more marketable when it comes to job opportunities.